2019
DOI: 10.1002/hfm.20819
|View full text |Cite
|
Sign up to set email alerts
|

An advanced human error assessment approach: HEART and AV‐DEMATEL

Abstract: Human error assessment and reduction technique (HEART) is one of the most commonly used human error assessment approaches which computes human error probability (HEP) to prioritize errors related to human actions. HEART is a powerful tool considering error producing conditions (EPCs) which increase the HEP for generalized task versions named as generic task types (GTTs). HEART can give a solution including prevention of human-related errors (HREs) and reduction of the HREs' impacts via implementing additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Origin and Applied Domain-HEART was initially proposed based on data collected in a nuclear power plant by Williams, (1988) to evaluate HEP based on human performance associated with PIFs. This method has been applied in both manufacturing (chemical, aviation, and railway) (Can and Delice, 2020;Casamirra et al, 2009;Pratiwi et al, 2019) and medical sectors (Aalipour et al, 2016;Can and Delice, 2020;Kirwan, 1997;Lyons et al, 2004;Kumar, Rajakarunakaran, and Prabhu, 2017).…”
Section: Human Error Assessment and Reduction Technique (Heart)mentioning
confidence: 99%
See 1 more Smart Citation
“…Origin and Applied Domain-HEART was initially proposed based on data collected in a nuclear power plant by Williams, (1988) to evaluate HEP based on human performance associated with PIFs. This method has been applied in both manufacturing (chemical, aviation, and railway) (Can and Delice, 2020;Casamirra et al, 2009;Pratiwi et al, 2019) and medical sectors (Aalipour et al, 2016;Can and Delice, 2020;Kirwan, 1997;Lyons et al, 2004;Kumar, Rajakarunakaran, and Prabhu, 2017).…”
Section: Human Error Assessment and Reduction Technique (Heart)mentioning
confidence: 99%
“…Reported Validation-Studies have reported this model was validated by Kirwan, (1997) at the same UK nuclear power plant that the model was proposed. Different studies were validated the HEART model by trying in different industries such as maintenance of the production process (Aalipour et al, 2016), steam boiler control process (Can and Delice, 2020), railway maintenance , and in the experimental nuclear physic facility (Giardina et al, 2019).…”
Section: Reported Model Advantages and Disadvantages-mentioning
confidence: 99%
“…Can [5] and Delice [6] first proposed integrated effect matrix for DEMATEL to advance HEART for steam boiler working process. Can and Delice [22] suggested HEART and advanced version of DEMATEL (AV-DEMATEL) integration to evaluate machine related errors and human related errors in a steam boiler working process. They also advanced a new aggregating operator to compute PEP.…”
Section: Scientific Literature Reviewmentioning
confidence: 99%
“…The human error assessment and reduction technique (HEART) is one of the most widespread techniques because it is easy to learn, reliable, and has a straightforward mechanism but has a moderate accuracy [ 17 , 18 , 24 ]. This technique is flexible and has been used to estimate the HEP in many industries, including railways [ 18 , 19 ], shipping [ 20 , 21 ], manufacturing [ 22 ], and information [ 23 ]. The HEP obtained by the HERAT has three parts including, Generic Task Type (GTT), Error-Producing Conditions (EPC), and Assessed Proportion of Affect (APOA).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies tried to improve the certainty of the HERAT technique. Fuzzy-HEART [ [24] , [25] , [26] ], a hybrid HEART based on AHP [ 20 ], Fuzzy analytic network process [ 27 ], HEART and AV-DEMATEL [ 22 ], HEART combined with improved analytic hierarchy process [ 28 ]. The classical fuzzy approach does not consider the self-confidence of experts and has an uncertainty in the extracted human opinions [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%